Work Pressure and Safety Behaviors among Health Workers in Ghana: The Moderating Role of Management Commitment to Safety - Kwesi Amponsah-Tawaih; Michael Appiah Adu (Elsevier, 2016)
Background: safety and healthy working environment has received numerous research attention over the years. Majority of these researches seem to have been conducted in the construction industry, with little attention in the health sector. Nonetheless, there are couple of studies conducted in Africa that suggest pressure in hospitals. Therefore the aim of the study was to examine how pressure influence safety behavior in the hospitals. With reference to the relevance of safety behavior in primary health care delivery, there was the need for the study. Method: Data was obtained from 422 public hospital employees. Respondents were assured that all information would be kept confidential to increase the response rate and acquire more accurate information. Collection of questionnaires from participants took four weeks (20 working days), after which the data was analyzed. Results: The result of the study showed that work pressure correlated negatively with safety behavior. General safety climate significantly correlated positively with safety behavior and negatively with work pressure, although the effect size for the latter was smaller. Hierarchical regression analysis showed management commitment to safety to moderate the relationship between work pressure and safety behavior. Conclusion: When employees perceive safety communication, safety systems and training to be positive, they seem to comply with safety rules and procedures than voluntarily participate in safety activities.